Study the State of Architectural Changes in Residential Buildings in the UA World Heritage Area in Luang Prabang City - Manithong, Phatthaing; Vongvilay, Xayaphone; Phanthavong, Khamxaiy (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research focuses on studying the conditions of architectural changes within residential houses in the Old Town Conservation Zone (UA). The objective of the study is to assess the state of architectural transformations in residential buildings located in the Old Town Conservation Zone (UA). This is a qualitative study, with the target group consisting of five residential houses in Pa Kham Village, Luang Prabang City, which were constructed from the past to the present. The data were analyzed through synthesis of empirical data and interpreted in terms of architectural characteristics. The results of the study are as follows: The conditions of architectural changes in residential houses within the Old Town Conservation Zone (UA) were found to occur in three periods: the phase I (1995–2005) marked the beginning of conservation. Its key characteristics represent the initial stage of management, with noticeable changes to building facades (exterior) and clearly observable interior modifications. The phase II (2005–2015) was characterized by economic growth and tourism expansion. The main features included strong economic incentives, functional transformations, complex interior changes (such as electrical and water supply systems), and the use of substitute materials, and the Phase III (2015–present) reflects stricter management and increasing modernization. Its notable characteristics include the enhancement of regulatory measures, the integration of old and new buildings (fusion), and challenges arising from building age and technological systems.